Welcome to Westonci.ca, where you can find answers to all your questions from a community of experienced professionals. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
n/2 - 2n/ 16 = 3/8
(n x 8 / 2 x 8 ) - (2n / 16) = 6 / 16
8n / 16 - 2n / 16 = 6/ 1 6
8n - 2n = 6
6n = 6
n = 6 / 6 = 1
n = 1
(n x 8 / 2 x 8 ) - (2n / 16) = 6 / 16
8n / 16 - 2n / 16 = 6/ 1 6
8n - 2n = 6
6n = 6
n = 6 / 6 = 1
n = 1
We hope this information was helpful. Feel free to return anytime for more answers to your questions and concerns. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.